MORPHOTECTONICS OF THE PSATHOPYRGOS ACTIVE FAULT, WESTERN CORINTH RIFT, CENTRAL GREECE - Tsimi, Ch.; Ganas, A.; Soulakellis, N.; Kairis, O.; Valmis, S. (Bulletin of the Geological Society of Greece, 2007)
The study area is located on the western part of the Gulf of Corinth which is considered as a paradigm of an active rift system in Greece. This rift was formed by normal slip on big faults which extend the crust of the Earth in the N-S direction. The morphotectonic indices (hypsometric curve, hypsometric integral, drainage basin asymmetry, ratio of valley floor width to valley height) have been estimated using the 20-m digital elevation model of this area and the ARC software. The normal faults of the study area have been extracted by use of a DEM mosaic of 20-m pixel size, satellite images from Landsat 7 ETM+ and SRTM 90m. Our results highlight the recent activity of the Psathopyrgos normal fault on the basis of a series of morphotectonic evidence and suggest the existence of a single fault segment for a distance of 16 km.